Hubungan Tingkat Pengetahuan Tentang Anemia Dengan Kejadian Anemia Pada Ibu Hamil - Lindung Purbadewi; Yuliana Noor Setiawati Ulvie (Jurnal Gizi, 2013)
Mother Mortality Rate 2003 in Indonesia is still high which is 307/100.000 live birth. The main cause of maternal death inter alia postpartum bleeding, eklampsi, infection diseases, and placenta previa, which all of it have a source from iron deficiency anemia. The cohort register of pregnant mother at Public Health Service Moyudan state that the pregnant mother number 2007 is 377 person and 180 (47,75%) of pregnant mother experiences anemia and based on the introduction study it had found that 4 out of 5 pregnant mother did not have good knowledge about anemia.The Objective is To know the correlation of knowledge level about anemia with the anemia case on pregnant mother in Public Health Service Moyudan Sleman Yogyakarta number 2009. The Method is analytical descriptive research with cross-sectional method. The sample was taken by using accidental sampling technique of 42 persons. The data aboutcharacteristics and knowledge of pregnant mother were obtained from questionnaire, and Hb level data of pregnant mother was obtained from pregnant mother cohort register. It uses chi square analysis to know the correlation between knowledge level of anemia case with anemiacase. Most of respondents (90,5%) are health include in reproductive age (20-35 years old) is 90,5%, the respondents of high school education level (SMA, SMK/equal level) are 61,9% and unemployed pregnant mothers are 59,5%. Percentage the knowledge level of respondentsabout anemia is equal between good and bad category which is 50% and the experience anemia of pregnant mother is 64,3%. The results of chi square analysis is p value 0,000 < 0,05 (p < α) with contingency coefficient rate of 0,480. There is middle level correlation between the knowledge level about anemia with anemia cases on pregnant mothers at Public Health Service Moyudan Sleman YogyakartaKeyword : Knowledge level, pregnant mother, anemia